1996
DOI: 10.1128/iai.64.2.606-610.1996
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin associated with the porcine intestinal mucosa is a receptor specific for K88ab fimbriae of Escherichia coli

Abstract: Putative receptors of Escherichia coli K88 fimbriae are either tightly membrane bound or an integral part of membranes. Thus, proteins associated with piglet small intestinal mucosae were solubilized by a detergent (deoxycholate). A 74-kDa glycoprotein (GP74) purified from enterocyte and brush border membrane preparations was specifically detected in vitro by K88ab fimbriae. GP74 was recognized only in the mucosae of phenotypically adhesive animals. Metaperiodate treatment abolished the recognition, indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…Transferrin a is an iron ion transporter and an important factor in homeostasis maintenance, in which the iron ion absorption effect is known to attenuate bacterial proliferation. Transferrin a is also abundant in mucosal tissues and considered to inhibit bacterial survival (32,33). Moreover, the transferrin gene has been identified in several fish species, including the Japanese medaka, and is known to be induced at the transcriptional level upon bacterial infection stress (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Transferrin a is an iron ion transporter and an important factor in homeostasis maintenance, in which the iron ion absorption effect is known to attenuate bacterial proliferation. Transferrin a is also abundant in mucosal tissues and considered to inhibit bacterial survival (32,33). Moreover, the transferrin gene has been identified in several fish species, including the Japanese medaka, and is known to be induced at the transcriptional level upon bacterial infection stress (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…The locus controlling susceptibility towards ETEC F4 strains ab and ac (F4ab/ac) has been consistently mapped to pig chromosome (SSC) 13q41 (Python et al 2002;Jørgensen et al 2003), and the positional candidate genes are most likely those coding for some transferrins or mucin-like sialoglycoproteins (Grange & Mouricout 1996;Grange et al 1998Grange et al , 2002. Transferrin receptor (TFRC) was assigned to SSC13q41 by radiation hybrid mapping (Van Poucke et al 2001), and was hence considered as a positional candidate gene for ETEC F4ab/ac receptor (Python et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Many research groups have reported the identification of putative K88 fimbrial adhesin receptors in both intestinal brush border (9,12,17,19,35) and intestinal mucus (5,19,21,37) preparations. In contrast to many of the other K88 receptors identified, IMTGP-1 and IMTGP-2 are detected only in adhe-sive phenotypes of pigs; consequently, it is very likely that these receptors are important in the in vivo attachment of K88ab and K88ac ETEC to porcine intestine (4,8,9,28).…”
Section: Discussionmentioning
confidence: 99%